Similarities and Differences between Multisystem Inflammatory Syndrome in Children (MIS-C) and Kawasaki Disease Shock Syndrome - Jin Lee; Beom Joon Kim; Kyoung-Soon Cho; Jung Woo Rhim; Soo-Young Lee; Dae Chul Jeong (MDPI AG, 2023)
This study aimed to investigate the characteristics of COVID-19-associated multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease shock syndrome (KDSS) and to compare the similarities and differences between the two diseases. The incidence of KDSS and MIS-C was also estimated. Medical records of patients diagnosed with MIS-C or KDSS at four hospitals from January 2013 to December 2022 were retrospectively reviewed. Thirty-one patients were enrolled in the study in either an MIS-C group (n = 22) or a KDSS group (n = 9). The incidence of KDSS in KD was 0.8% (9/1095) and the incidence of MIS-C versus KD was 10.2% (22/216). Compared with the MIS-C group, the KDSS group had longer hospital stays and more severe systemic inflammation (e.g., anemia, elevated C-reactive protein, hypoalbuminemia, and pyuria) and organ dysfunction (e.g., number of involved organs, shock, vasoactive infusion, and intensive care unit admission). All patients in the MIS-C group, but none in the KDSS group, including two patients during the COVID-19 pandemic, had laboratory evidence of SARS-CoV-2 infection. MIS-C and KDSS shared demographic, clinical, and laboratory characteristics; organ dysfunction; treatment; and outcomes. Overall severity was more severe in patients with KDSS than in those with MIS-C. The most important difference between MIS-C and KDSS was whether SARS-CoV-2 was identified as an infectious trigger.